Meso/macro scale response of the comingled glass polypropylene 2-2 twill woven fabric under shear pre-tension coupling. (15th March 2020) - Mei, Ming; He, Yujia; Yang, Xujing; Wei, Kai; Mo, Fuhao
Abstract: Pre-tension is well known as an effective approach to suppress forming defects caused by excessive shearing in manufacture process of the fabric reinforced composites. While, the coupling between shear and pre-tension of the fabrics is not thoroughly understood. Here, this work aims to explore and understand the meso/macro scale response of the comingled glass-polypropylene 2-2 twill woven fabric under shear pre-tension coupling. A self-developed picture frame fixture including a concise approach to apply pre-tension in shear experiments of the fabric was originally developed. Then, systematical shear experiments confirm that the critical shear angle of the fabric is 40°, as the fabric suffers in-plane complex deformations when the shear angle is above 40°. Additionally, the pre-tension significantly enlarges the shear force when the shear angle is lower than critical value of 40°. In view of mesoscopic scale, the pre-tension suppresses the undulation of the un-sheared fabric surface, revealing an enhancement of the coupling effect at the initiation of the shear deformation. Besides, the pre-tension also reduces the variation of yarn width. While, these mesoscopic effects caused by pre-tension are not pronounced when it is higher than 1.2 N/mm. The devised picture frame fixture and the exploration of the shear pre-tension coupling behavior provide an important experimental basis to the purpose of suppressing forming defect and to raise the manufacture efficiency of the fabric reinforced composites.